Improving Young Learners’ Vocabulary Through Peppa Pig Cartoon - Husnil Khotimah (Yayasan Al-Afif, 2026)
This study aims to improve English vocabulary mastery among 3rd grade students at MI Rohmatul Ummah through the use of the Peppa Pig cartoon, specifically the “Fruit” episode. This qualitative research involved 27 students, consisting of 12 males and 15 females. The primary issue addressed is the low interest and limited vocabulary range typical of young learners at the elementary level. Data were collected through participant observation and interviews using the paused-viewing technique. The results indicate that students were able to identify various types of fruit, distinguish between fruits and vegetables, and accurately imitate expressions of preference. The use of animation proved effective in creating a low-anxiety learning environment and accelerating the retention of new vocabulary through visual and auditory associations.